Insights into the Organotemplate-Free Synthesis of Zeolite Catalysts - Wang, Yeqing; Wu, Qinming; Meng, Xiangju; Xiao, Feng-Shou (Engineering (Beijing, China), 2017)
As the most important nanoporous material, zeolites, which have intricate micropores, are essential heterogeneous catalysts in industrial processes. Zeolites are generally synthesized with organic templates under hydrothermal conditions; however, this method is environmentally unfriendly and costly due to the formation of harmful gases and polluted water. This article briefly summarizes the role of organic templates and describes designed routes for the organotemplate-free synthesis of zeolites, aided by zeolite seeds and zeolite seeds solution. Furthermore, this review explicates that the micropore volume decreases with an increase of the Si/Al ratios in the organotemplate-free synthesis of zeolite products, where Na+ exists as an alkali cation. This feature is very important in directing the synthesis of zeolite catalysts with controllable Si/Al ratios under organotemplate-free conditions, and is thus important for the efficient design of zeolites.